Nanomaterials exposure as an occupational risk in metal additive manufacturing. (October 2019) - Sousa, M; Arezes, P; Silva, F
Abstract: Metal Additive Manufacturing (AM) is a process of joining metallic materials based on 3D model data, aiming the manufacture of three dimensional parts by the successive addition of material, usually layer upon layer. This technology is nowadays seen as an emerging one, showing exceptional perspectives of growth, being able to produce parts in various materials such as precious metals (for example gold, silver and platinum) and several metal alloys, such as aluminium, titanium, nickel, cobalt and magnesium based alloys, among others. However, as the range of feedstock materials, technologies and applications increases, so do the concerns about its impact on health and safety of those who are exposed to the particles emitted during these processes, particularly when AM uses metal powder. Regarding emissions, studies thus far show that nanomaterials are emitted during AM processes, a fact that rises the concern about its impacts and enhances the complexity of risk management on these processes. When risk management aims nanoscale, it becomes a true challenge as it deals with several different nanomaterials and the lack of systematic and standardized risk assessment methodologies. At this scale, risk management raises many doubts regarding the selection of quantitative or qualitative approaches, the identification, characterization and quantification of nanomaterials, the definition of occupational exposure limits and the outlining of control measures. Having this conscience, a review was developed to summarize some of the recent developments in the field of risk management of occupational exposure to nanomaterials during metal additive manufacturing. Additionally, this review emphasizes the need for more investigation about risks regarding nanomaterials in workplaces, which is essential to ensure workers' safety conditions and preserve their health, as well as to make conscious decisions on risk assessment, public health, medical monitoring and control measures, namely the adoption of personal protective equipment.